Elevated levels of per- and polyfluoroalkyl substances in Cape Fear River Striped Bass (Morone saxatilis) are associated with biomarkers of altered immune and liver function - T.C. Guillette; James McCord; Matthew Guillette; M.E. Polera; Kyle T. Rachels; Clint Morgeson; Nadine Kotlarz; Detlef R.U. Knappe; Benjamin J. Reading; Mark Strynar; Scott M. Belcher (Environment International, 2020)
Per- and polyfluoroalkyl substances (PFAS) are anthropogenic chemicals of concern that persist in the environment. Environmental monitoring revealed high concentrations of hexafluoropropylene oxide dimer acid (HFPO-DA) and other novel PFAS in the lower Cape Fear River; however, there is limited information on PFAS exposures and effects of this contamination on aquatic biota. Serum concentrations of 23 PFAS in Striped Bass (Morone saxatilis) from the Cape Fear River (n = 58) and a reference population from an aquaculture laboratory on the Pamlico/Tar watershed (n = 29) were quantified using liquid chromatography and high-resolution mass spectrometry, and correlations between PFAS concentrations and health-related serum biomarkers were evaluated. Perfluorooctane sulfonate, the predominant PFAS in Cape Fear River Striped Bass serum, was detectable in every sample with serum concentrations reaching 977 ng/mL. Perfluorononanoic and perfluorodecanoic acid were also detected in all samples, with perfluorohexanesulfonic acid present in >98% of the samples. HFPO-DA (range <0.24–5.85 ng/mL) and Nafion byproduct 2 (range <0.2–1.03 ng/mL) were detected in 48% and 78% of samples, respectively. The mean total PFAS concentration found in domestic Striped Bass raised in well-water under controlled aquaculture conditions was 40 times lower, with HPFO-DA detected in 10% of the samples, and Nafion byproduct 2 was not detected. The elevated PFAS concentrations found in the Cape Fear River Striped Bass were associated with biomarkers of alterations in the liver and immune system.